Virus Caused Imbalance of Type I IFN Responses and Inflammation in COVID-19 - Zhang, Jintao; Zhao, Chunyuan; Zhao, Wei (Frontiers in Immunology, 2021)
The global expansion of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has emerged as one of the greatest public health challenges and imposes a great threat to human health. Innate immunity plays vital roles in eliminating viruses through initiating type I interferons (IFNs)-dependent antiviral responses and inducing inflammation. Therefore, optimal activation of innate immunity and balanced type Ⅰ IFN responses and inflammation are beneficial for efficient elimination of invading viruses. However, SARS-CoV-2 manipulates the host’s innate immune system by multiple mechanisms, leading to aberrant type Ⅰ IFN responses and excessive inflammation. In this review, we will emphasize the recent advances in the understanding of the crosstalk between host innate immunity and SARS-CoV-2 to explain the imbalance between inflammation and type Ⅰ IFN responses caused by viral infection, and explore potential therapeutic targets for COVID-19.